Avaliação das etapas do cuidado contínuo de paciente com HIV/Aids, atendido em serviço de atendimento especializado em Aids (SAE), no município de Santos- SP. 2009 a 2013 - Golegã, Alcino Antonio Campos (2017)
By 2013, UNAIDS has updated its global targets for the year 2020 for HIV-positive people; In which 90% of infected people are tested and will know that they are HIV, 90% of HIV-positive people are receiving ARV treatment, and that 90% of those people must achieve viral suppression to end the transmission of the epidemic by 2030 A The cascade of HIV continuous care is commonly represented as a bar chart that counts the number of individuals engaged in providing services to People Living with HIV / AIDS at all stages of ongoing care. The loss of individuals occurs at different points, which means that the number of people observed in each stage of the cascade is smaller than in the previous one. The objective of this study is to evaluate the steps of the continuous care of patients assisted in a public service specialized in HIV / AIDS (SAE - adult), in Santos, São Paulo, between 2009 and 2013. Methodology: This study was designed according to as standards for the construction of the Continuous Care Cascade for HIV patients, as recommended by the Brazilian Ministry of Health. It is a mixed study of Temporal and Longitudinal series, Transverse, successive and sequential cross-sections are drawn up in continuous care, represented by columns, for the years 2009 to 2013; For study purposes the study population are all HIV patients enrolled in SECRAIDS, from January 2, 2009 to December 30, 2013. Results: A total of 1,179 patients enrolled in SAE - (224), 2010 (253), 2011 (240), 2012 (216) and 2013 (246), we observed that even with a heterogeneous population, we perceive a certain homogeneity in the distribution of socio-demographic factors. In relation to sex we have a predominance of the masculine in relation to the feminine, in all the years and a variation in the reason of sex, that goes of 1.7 until 3 men for each woman. Regarding the category of exposure, each year presents the heterosexual form as preponderant with more than 50% of the cases. Regarding the age group, we noticed that the age group of 30 to 39 holds the largest number of people in every year. In the category of schooling the subgroup with more than 10 years of study concentrates the largest contingent of people. In relation to race / color, it presents above 60% of the cases of race / color White and in average 33% of browns and blacks. However, in the case of the Marital State, the subgroup Singular, more than 50% of the cases, followed by married / amassed with 30% of the cases. Although linkage to service and access to treatment increased during the period, there was a significant decrease in viral suppression. Viral suppression is directly linked to the quality of service offered to HIV patients, since it is directly linked to the link that the service establishes for this patient, as well as the possibility of performing an integral treatment and also linked to the correct use of the medication. Thus we can add that it is necessary, a good adhesion of the patient to the service, the proposed treatment, the support offered, the continuous monitoring, the withdrawal of the medication, that is, the correct use and therapeutic control, that must be studied in other works.